Evaluating the Hepatoprotective Effects of Barley on Alloxan-Induced Liver Damage in Diabetic Male Wistar Rats - Dinata, Erica; Meldawati, Meldawati; Halim, Yeni (Sarana Ilmu Indonesia (salnesia), 2024)
Type 2 diabetes mellitus often leads to non-alcoholic fatty liver disease, affecting 69-74% of patients. Barley (Hordeum vulgare) offers a potential therapeutic alternative with safer interventions. This study aimed to explore the effects of barley on liver histopathology in alloxan-induced male Wistar rats and compare it with metformin. The research was conducted using a laboratory experimental design with 36 male Wistar rats divided into six groups: normal control, negative control (alloxan induction without treatment), positive control (metformin), and three treatment groups with variations in barley administration. Treatment group 1 received barley before and after alloxan induction, treatment group 2 received barley and standard feed after alloxan induction, and treatment group 3 received standard feed mixed with barley after alloxan induction. Barley was administered for 28 days, and histopathological analysis was performed at the end of the study. Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests. The results showed that barley was able to improve liver cell damage, although not as effectively as metformin. The positive control group with metformin showed an average liver damage score of 148,33 with 53,03% normal cells and 15,28% necrotic cells. In contrast, the barley treatment groups showed average liver damage scores of 169,67 and 159,67. Thus, barley can improve liver histopathology in alloxan-induced rats, highlighting its potential as a safe herbal therapy for preventing and managing liver damage caused by oxidative stress in diabetes mellitus.